2018
DOI: 10.1080/24749508.2018.1558025
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the political ecology of forced migration and deforestation through a multi-algorithm classification approach: the case of Rohingya displacement in the southeastern border region of Bangladesh

Abstract: Compared with numerous existing forced migration scenarios across the globe, migration from Myanmar to Bangladesh through southeastern border region is unique at least for three reasons-(i) very large number of migrants have been displaced to (ii) a very small area in (iii) a relatively short period of time, creating an obvious cumulative impact on forest cover area of the host country. Therefore, this study aims to analyze the dynamics of refugee migration and deforestation in Bangladesh. Satellite images of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…The Classification and Regression Tree (CART) (Breiman et al 2017) predictive model was used for the analysis. CART has been utilised for similar purposes in recent times (Ahmed et al 2019). Since assignment of pixels to disjoint classes translates into the target variable taking discrete values, the model is more specifically addressed as a classification tree which is a specialised form of decision trees.…”
Section: Algorithmmentioning
confidence: 99%
“…The Classification and Regression Tree (CART) (Breiman et al 2017) predictive model was used for the analysis. CART has been utilised for similar purposes in recent times (Ahmed et al 2019). Since assignment of pixels to disjoint classes translates into the target variable taking discrete values, the model is more specifically addressed as a classification tree which is a specialised form of decision trees.…”
Section: Algorithmmentioning
confidence: 99%
“…This algorithm is rarely used for the classification of remote sensing data [55], especially for multi-class classification. However, it is a well-known method in studies of species distributions and habitat models [53,56,57], and it has been reported to perform better in one-class or binary classification applications than other algorithms, such as the support vector machine method [58].…”
Section: Supervised Classificationmentioning
confidence: 99%
“…Random forest Random Forest (Breiman, 2001) is also an ensemble model, where the prediction is an aggregation of the outputs from the individual decision trees. The algorithm has been used for land cover classification of the southeastern border region of Bangladesh (Ahmed, Islam, Hasan, Motahar & Sujauddin, 2019;Hassan, Smith, Walker, Rahman, & Southworth, 2018). As shown in Equation 11, the outputs of the individual weak learners are averaged.…”
Section: Preprocessingmentioning
confidence: 99%